AbobotulinumtoxinA (Dysport®) Improves Function According to Goal Attainment in Children With Dynamic Equinus Due to Cerebral Palsy. (April 2017) - Tilton, Ann; Russman, Barry; Aydin, Resa; Dincer, Umit; Escobar, Raul G.; Kutlay, Sehim; Lipczyk, Zbigniew; Velez, Juan Carlos; Grandoulier, Anne-Sophie; Tse, Anissa; Picaut, Philippe; Delgado, Mauricio R.
This secondary analysis of a large (n = 241), randomized, double-blind study evaluated the efficacy of 2 doses of abobotulinumtoxinA + standard of care (SOC) versus placebo + SOC in enabling children with dynamic equinus due to cerebral palsy to achieve their functional goals using Goal Attainment Scaling. Most parents/caregivers selected goals targeting aspects of gait improvement as most relevant. Mean (95% confidence interval) Goal Attainment Scaling T scores at week 4 were higher for both abobotulinumtoxinA groups versus placebo (treatment difference vs placebo: 10 U/kg/leg: 5.32 [2.31, 8.32], P = .0006, and 15 U/kg/leg 4.65 [1.59, 7.71], P = .0031). Superiority of both abobotulinumtoxinA doses versus placebo was maintained at week 12. Best goal attainment T scores were higher in the abobotulinumtoxinA groups versus placebo for the common goals of improved walking pattern, decreased falling, decreased tripping, and improved endurance. These findings demonstrate that single injections of abobotulinumtoxinA (10 and 15 U/kg/leg) significantly improved the ability of pediatric cerebral palsy patients to achieve their functional goals.